NUMERICAL REVOLUTION : GPT CHATBOTS IN LANGUAGE ACQUISITION AND CROSS-CULTURAL LEARNING - SOUALAH MOHAMMED Hayet (Ziglôbitha)
Abstract : The introduction of digital technology, such as GPT chatbots, is revolutionizing the teaching of foreign languages and providing new opportunities to learners and teachers. Still, an important question remains: how can we make sure that digital tools for language teaching fit learners’ needs in terms of teaching and culture? In practice, GPT chatbots are helpful because they can automate common teaching tasks, relieving teachers and making them concentrate on the most important and creative parts of teaching. Furthermore, GPT chatbots allow students to have real conversation in the language, giving them practice and improving their communication skills (Afial, 2025). For example, universities can use these chatbots in their classes so students can keep practicing their language, get helpful feedback, and work with teaching materials made just for them (Afial, 2025). As part of this study, you can look at how students are using GPT chatbots in classrooms by checking how often they use them and how well they talk with them, and you can compare that with how they normally use other kinds of educational technology. You can also give students surveys to find out what they think about using chatbots, what problems they might have, and how they feel it affects their learning and motivation. Additionally, surveys can be given to get students' opinions about chatbots, what problems they have, and how they think the chatbots affect their learning and motivation. The findings from these observations and surveys will tell us how effective GPT chatbots are and what changes are needed to help them benefit students the most. The study is necessary to learn about modern learning methods and improve the teaching approaches that are used today. Using the collected data, it is possible to improve the use of GPT chatbots and make them more significant in different educational settings, taking into account the needs and expectations of learners.